Proportional Exploration of Stock Exchange Data Corresponding to Various Sectors Using Apache Pig - Yogesh Kumar Gupta, Sumun Kamboj, Ashok Kumar (International Journal of Advanced Science and Technology, 2020)
The word “Big Data” referred to the voluminous amount of data which cannot be processed utilizing conventional approaches due to intricacy and its multifarious nature. With recurrent increment of internet users, prodigious amount of data engendered in our quotidian life which need to be processed with very highly efficient implements thus consequential insights can be extracted facilely. There are sundry implements which can avail us to analyze data; Hadoop is considered as one of the famous implements which consist of multiple core components to enhance the robustness. Apache Pig is most prominent core component of Hadoop. In this paper, we accentuate the utilization of Apache pig which compares the stock exchange data of diverse sectors designated IT, Oil and Sugar. In this study, we have gone through the yearly data from 2013-2018. We have taken 4 companies from each sector to define the comparative analysis among them by calculating low, average and high prices of stock and additionally perceive mapper and reducer time. Keywords: Apache pig, big data, Hadoop, stock exchange data, stock sectors.